Tingkat Kerendahan Hati Siswa SMP - Devi Permatasari (JKI (Jurnal Konseling Indonesia), 2016)
Humility is one of the characters themselves the most fundamental and important to be grown, trained and familiarized with students so that can be applied in everyday life. Humility is needed to acquire other virtues because it makes people aware of the imperfections, dare to admit mistakes and take responsibility for what you have done, and make people try to be a better person. This study uses a descriptive-quantitative methodology to identify the level of humility junior high school students (SMP) will specifically identified on the basis of sex or gender differences. This study used random and purposive random sampling of 64 junior high school students. The study identified 6.3% junior high school students are at a very high level of humility, 48.4% junior high school students are at a high level of humility, 20.3% junior high school students are at a level of humility moderate, and 25% of junior high school students are at low levels of humility. So that the average junior high school students are at a level of humility is high (48.4%). Furthermore, hypothesis testing using two independent samples t shows the t value is 0, 725 with significance 0, 039. Therefore, the significance of 0, 039 <0.05 then it is concluded that there are significant differences between the level of humility boys and women in other words there is a significant difference of humility based on gender.